Non-linear dynamic analysis of composite conical shell structures - Hakim, S. Sultan; Mahdi, E.; Hamouda, A.M.; Mokhtar, A.S.; Chong, W.T.; Irfan Anjum (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.